Religion and the hermeneutics of contemplation - Phillips, D. Z. (Dewi Zephaniah) (Cambridge University Press, 2001)
Leading philosopher of religion D.Z. Phillips examines the conceptual assumptions of atheistic thought in the work of leading thinkers including Frazer, Feuerbach, Marx, Freud and Durkheim. Extending Phillips' earlier work, Religion Without Explanation, this book makes an important new contribution to the philosophy of religion and related disciplines.